In Great Company How to Spark Peak Performance By Creating an Emotionally Connected Workplace. - Carter, Louis; Goldsmith, Marshall (McGraw Hill-Ascent Audio, 2019)
The manager's solution to boosting business growth and team effectiveness: when employees are emotional connected to the organization, personal performance skyrockets.